Prevalence of pharmacogenomic variants affecting the efficacy of clopidogrel therapy in the Hispanic Community Health Study/Study of Latinos cohort. (6th December 2018) - Melin, Kyle; Moon, Jee-Young; Qi, Qibin; Hernandez-Suarez, Dagmar F; Duconge, Jorge; Hua, Simin; Gonzalez, Sara; Zeng, Donglin; Kaplan, Robert C
Purpose: Although clopidogrel is the most widely used oral P2Y12 receptor antagonist, up to 10% of acute coronary syndrome patients treated with clopidogrel will experience a recurrent myocardial infarction and 2–3% will experience stent thrombosis within 1 year. The purpose of this research is to describe the prevalence of pharmacogene variants associated with clopidogrel responsiveness ( CYP2C19, B4GALT2, ABCB1, PON1, CES1  and P2RY12 ) in Hispanic/Latino patients of diverse backgrounds.Methods: Minor allele frequencies of nine variants from participants of Hispanic Community Health Study/Study of Latinos were compared between subpopulations as well as to continental ancestry references using z-test for independent proportions.Results: MAFs for six out of nine variants differed between Caribbean and Mainland subpopulations (p < 0.05). Compared with European reference group, MAFs of ABCB1, CES1  and PON1 were higher in Hispanic Community Health Study/Study of Latinos, whereas B4GALT2 and CYP2C19*2 and *17 were lower.Conclusion: Significant differences in the prevalence of most pharmacogenomic variants related to clopidogrel response provide a foundation to better inform ongoing and future clinical studies of clopidogrel pharmacogenetics in the US Hispanic/Latino populations.